THE IMPORTANCE OF DIDACTIC GAMES IN THE DEVELOPMENT OF THINKING OF PRESCHOOL CHILDREN - Muyassar N. Esonova (Oriental Journal of Education, 2023)
Reforms carried out in the preschool education system for the development of children's thinking, the stages of development of thinking in preschool children and their specific importance, and the advantages of using didactic games in the development of children's thinking.